English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(3x -1)(2x+3)

GCSE Maths revision, thanks

2007-04-03 06:57:34 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

the wayto do these equations is to multiply every term in the first bracket by every term in the 2nd bracket.
So :
3x times 2x + 3x times 3
-1 times 2x + -1 times 3

which gives 6x squared + 9x
-2x -3

and since 9x-2x = 7x

the answer is :
6x squared +7x -3

an easy way to check your answer is to put a simple figure (like 2) in place of x and see if the original equation gives the same answer as the new one
so original = (6-1) x (4+3) = 5 x 7 = 35

and the new equation = (6 x 2 x 2) + (7 x 2) - 3
= 24 + 14 - 3 = 35

since both equations have given the same result you have checked the answer. If they gave different results then you know you have made a mistake somewhere and should go back.

2007-04-03 07:07:29 · answer #1 · answered by MARTIN B 4 · 0 0

(3x -1) (2x+3)
= 6x^2 + 9x - 2x - 3
= 6x^2 + 7x - 3


(you multiply the 3x*2x and 3x*3 and -1*2x and -1*3 and add them together)

2007-04-03 14:00:32 · answer #2 · answered by tonberry79 3 · 0 0

3x(2x+3) -1(2x+3)
= 6x^2 + 9x -2x -3
= 6x^2 +7x -3

2007-04-03 14:00:10 · answer #3 · answered by hustolemyname 6 · 0 0

FOIL

(3x - 1)(2x + 3) =

6x² - 2x + 9x - 3 =

6x² + 7x - 3

- - - - - - - - -s-

2007-04-03 14:21:19 · answer #4 · answered by SAMUEL D 7 · 0 0

6x squared + 7x -3

2007-04-03 14:02:44 · answer #5 · answered by Anonymous · 0 0

Order of opperations...

2007-04-03 14:02:55 · answer #6 · answered by stephen b 1 · 0 0

fedest.com, questions and answers